Sosialisasi Pengawasan Partisipatif untuk Masyarakat Pesisir Tanggetada dalam Pemilihan Bupati dan Wakil Bupati Kabupaten Kolaka Tahun 2024 - Adhe Ismail Ananda; Nurfadhillah Syam; Syamsul Rijal; Basrawi (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The socialization initiative about participatory oversight for the coastal town of Tanggetada in the 2024 Election for Regent and Deputy Regent of Kolaka Regency seeks to improve public comprehension and engagement in the electoral monitoring process. This program engaged 47 participants, comprising community leaders, youth, and representatives from fishing groups, utilizing tactics such as lectures, interactive discussions, simulations, and the dissemination of instructional materials. Evaluation results revealed that 90% of participants demonstrated enhanced understanding, with 70% attaining a superior level of comprehension. Participants expressed favorable opinions of the employed methodologies, especially simulations and talks, which were deemed pragmatic and comprehensible. Nevertheless, 10% of participants still necessitate further support. This initiative effectively heightened community understanding on the significance of transparency and integrity in elections and equipped people to actively participate in oversight activities. Subsequent proposals entail enhanced socializing and mentorship, particularly for populations in isolated regions